2015
DOI: 10.48550/arxiv.1505.08094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toroidality and projective-planarity of intersection graphs of subgroups of finite groups

R. Rajkumar,
P. Devi

Abstract: Let G be a group. The intersection graph of subgroups of G, denoted by I (G), is a graph with all the proper subgroups of G as its vertices and two distinct vertices in I (G) are adjacent if and only if the corresponding subgroups having a non-trivial intersection in G. In this paper, we classify the finite groups whose intersection graph of subgroups are toroidal or projective-planar. In addition, we classify the finite groups whose intersection graph of subgroups are one of bipartite, complete bipartite, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Remark 2.4. In [13], Zelinka proved that for any group G, α(I (G)) = m, where m is the number of prime order proper subgroups of G. In [9], the authors showed that Θ(I (G)) = α(I (G)). It is interesting to note that by Theorems 2.9 and 2.10, we have α(I (G)) = α(I c (G)) and Θ(I (G)) = Θ(I c (G)).…”
Section: Remark 22 Tarski Monster's Group Is An Infinite Non-abelian ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 2.4. In [13], Zelinka proved that for any group G, α(I (G)) = m, where m is the number of prime order proper subgroups of G. In [9], the authors showed that Θ(I (G)) = α(I (G)). It is interesting to note that by Theorems 2.9 and 2.10, we have α(I (G)) = α(I c (G)) and Θ(I (G)) = Θ(I c (G)).…”
Section: Remark 22 Tarski Monster's Group Is An Infinite Non-abelian ...mentioning
confidence: 99%
“…Inspired by these, there are several papers appeared in the literature which have studied the intersecting graphs on algebraic structures, viz., rings and modules. See, for instance [1,3,9,10,12] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Chiang-Hsieh et al [7] characterized the commutative rings of genus one. Very recently, Rajkumar and Devi [20] classified the finite groups whose intersection graphs of subgroups have (non)orientable genus one. Afkhami et al [2] classified planar, toroidal, and projective commuting and noncommuting graphs of finite groups.…”
Section: Introductionmentioning
confidence: 99%
“…Akhlaghi and Tong-Viet [4] studied the finite groups with K 4 -free prime graphs. Rajkumar and Devi [15] classified the finite groups with K 4 or K 5 -free intersection graphs of subgroups. In [8], Das and Nongsiang classified K 3 -free commuting graphs of finite non-abelian groups.…”
Section: Introductionmentioning
confidence: 99%